2023
DOI: 10.1088/2631-8695/acb902
|View full text |Cite
|
Sign up to set email alerts
|

A review on metallurgical features of hot-dip aluminized steel

Abstract: Among the various surface modification processes, the hot-dip aluminizing process has increasingly evoked considerable attention. This method has proved to be commercially cost-effective and technically better than galvanizing. In contrast to hot-dip aluminized steel components, galvanized components cannot be used in service conditions at elevated temperatures. During the last few years, intensive research by researchers has yielded new insights into metallurgical aspects of aluminized coating in as-dipped an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 150 publications
2
4
0
Order By: Relevance
“…These microstructures suggest that the Al 8 Fe 2 Si phase grew from the Fe 2 Al 5 phase during solidification. The phase compositions, microstructures, and growth sequences of the IMCs formed at the interface were similar to the results obtained in previous studies of Al-Si/(Fe or steel) bimetals [4,7]. Wang et al also confirmed that the IMC layer of Al-10Si/Fe bimetals aluminized at 700 • C for up to 30 min contains Fe 2 Al 5 , Al 8 Fe 2 Si, and Al 8 Fe 2 Si 2 [12].…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…These microstructures suggest that the Al 8 Fe 2 Si phase grew from the Fe 2 Al 5 phase during solidification. The phase compositions, microstructures, and growth sequences of the IMCs formed at the interface were similar to the results obtained in previous studies of Al-Si/(Fe or steel) bimetals [4,7]. Wang et al also confirmed that the IMC layer of Al-10Si/Fe bimetals aluminized at 700 • C for up to 30 min contains Fe 2 Al 5 , Al 8 Fe 2 Si, and Al 8 Fe 2 Si 2 [12].…”
Section: Resultssupporting
confidence: 85%
“…These microstructures suggest that the Al8Fe2Si phase grew from the phase during solidification. The phase compositions, microstructures, and grow quences of the IMCs formed at the interface were similar to the results obtained in ous studies of Al-Si/(Fe or steel) bimetals [4,7]. Wang et al also confirmed that the The metallographic specimens were taken from a cross-section 30 mm from the bottom of AC4C/STS420 bimetal and mechanically polished using standard procedures up to colloidal silica for 20 min.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Fan et al [70] provided a detailed summary of different coatings used for HS applications, but an updated summary has recently been provided in the review by Khan et al [12]. Dey et al [71] provided a list of reasons showcasing the benefits of hot-dip aluminized coatings over other types of coatings. Overall, the use of appropriate surface coatings is crucial to mitigate surface oxidation and corrosion in TWBs and PHS components.…”
Section: Coating Technologiesmentioning
confidence: 99%